How and why learning theories are taught in current Dutch teacher education programs. Identifying a gap between paradigm and reality in teacher education. (January 2022) - Meij, Erik; Smits, Anneke; Meeter, Martijn
Abstract: A teacher should arguably know about learning theories (LTs) in order to make daily pedagogical decisions. However, little literature exists on the role of LTs in teacher education. Eight Dutch teacher educators were interviewed on LTs in their curriculum. LTs were unanimously considered important but huge variation was found in what and how LTs are taught. Several functions of LTs were mentioned, with underpinning of pedagogical decisions using LT considered to be the essence of higher education. However, respondents doubted whether this is ever achieved. This suggests an additional paradigm – reality gap in teacher education. Highlights: The place and role of learning theory in teacher education are rarely investigated. Eight teacher educators in the Netherlands were interviewed on their curricula and vision concerning learning theories. Despite an agreed knowledge base, there is major variation in which learning theories are taught and how. Respondents believe teaching should be based on theory, but that teacher education cannot deliver such base can be achieved in initial teacher education. This additional theory-practice gap raises the question whether all teaching, as assumed, should be supported by theory.